Legal Implications for Home-Based Workers Following the Judicial Review Decision of the Constitutional Court of the Republic of Indonesia - Nova Septiani Tomayahu; Dedi Sumanto (The Indonesian Journal of International Clinical Legal Education, 2024)
This study aims to analyze the laws and regulations governing informal workers, especially home-based workers in Indonesia by examining decision No. 75/PUU-XX/2022 concerning the application for review of Law No. 13 of 2013 regarding Manpower against the 1954 Constitution in the Constitutional Court of the Republic of Indonesia. Understanding the legal status of informal workers in Indonesia is crucial. This research employed a normative legal method using statutory and analytical approaches. Data was collected using the document study method on secondary data, which was then analyzed qualitatively. Based on the research results, it was found that home-based workers are included in the informal sector, but Manpower Law has not yet accommodated them. This is because Indonesian law does not recognize home-based workers in the Job Creation Law or the Manpower Law, as it has not adopted international instruments on home-based workers. However, home-based workers still receive work agreements based on Article 1320 and Article 1338 of the Civil Code and protection in several laws and regulations. According to the Court, the government must specifically regulate home-based workers to accommodate every type of work in Indonesia.